Students' Perceptions of the Causes, Impacts, and Coping Strategies for Academic Procrastination at the Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara - Ritonga, Nurul Fitri; Utami, Ratih Yulistika (Universitas Muhammadiyah Sumatera Utara, 2027)
Abstract: Academic procrastination among university students is relatively high and has psychological impacts such as anxiety, depression, and stress. This study aims to determine the perceptions of students at the Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara (FK UMSU) regarding the causes, impacts, and strategies for managing academic procrastination. This study employed a mixed-methods approach with consecutive sampling involving 76 students. The quantitative findings showed that the majority of students, 59, had a moderate level of academic procrastination, while 11 had low and 6 had high levels. There were two categories of external factors (peers and time) and six categories of internal factors (behavioural, cognitive, physical, academic, interpersonal, and affective). Strategies for managing procrastination were classified into individual and group categories. Most FK UMSU students demonstrated a moderate level of academic procrastination. The contributing factors included peers and time management. Internal factors influencing procrastination were mood, motivation, task perception, academic ability, time management, and recreation. The impacts experienced by students covered behavioural, cognitive, physical, academic, interpersonal, and affective domains. Prevention strategies were categorised into individual and group approaches.